Ideologi, iman, dan gender: Relasi Pancasila dan agama dalam upaya mereduksi patriarki di Indonesia - Ziankha, Nazwa Ayudya (Maliki Interdisciplinary Journal, 2025)
Gender equality in Indonesia continues to face significant structural challenges, largely influenced by deeply rooted patriarchal culture within society. Gender inequality does not arise solely from biological differences but is shaped through long-standing social and cultural constructions that influence roles, expectations, and power relations between men and women. Political dynamics, economic structures, and gender-biased religious interpretations further reinforce these disparities, often limiting women’s access to education, employment, leadership, and decision-making spaces. In this context, Pancasila plays an essential role as the ideological and moral foundation for advancing gender equality. The values embedded in the second principle, Humanitarianism, and the fifth principle, Social Justice, affirm the importance of equality, dignity, and nondiscrimination for all citizens regardless of sex or gender. These values are reflected in national policies such as the ratification of CEDAW, gender mainstreaming programs, and the development of gender-responsive educational curricula. Within Islam, equality is a core principle that emphasizes the equal spiritual worth of men and women, although its practice has often been shaped by culturally biased interpretations. Therefore, strengthening collaboration between the government, educational institutions, religious organizations, and civil society is crucial to eliminate gender-based discrimination and create a more just and inclusive society.